An Analysis of Consumer Perceptions Towards Sustainable Fashion Trends - Pathak, Resham Raj; Dhungana, Dipendra; Acharya, Paras Mani (NPRC Journal of Multidisciplinary Research, 2025)
Background: Fashion globally is being held more accountable for its environmental impact, driving growth in sustainable alternatives such as thrifting, upcycling, and green brands. Attitudes of consumers are crucial to understanding the move toward a circular fashion economy, yet comprehensive examination of attitudes toward these fundamental areas is unexplored. Objectives: The current study aimed at profiling consumer attitudes across five dimensions of sustainable fashion: (1) thrifting preference, (2) upcycling interest, (3) being green knowledge, (4) environmental knowledge, and (5) social influence and convenience. Methods: A cross-sectional quantitative design was utilized with a self-report questionnaire of 236 participants. The instrument had 25 items answered on a 5-point Likert scale. Data analysis utilized descriptive statistics (mean, standard deviation, skewness, kurtosis) for testing central tendency and response distributions per construct. Findings: Results showed high environmental awareness (M=3.84-3.98) and theoretical support towards sustainable practices but huge intention-action gaps. Thrifting was valued for value (M=3.79) and novelty (M=3.52) above ecologic concerns (M=3.00). Upcycling elicited strong normative support (M=3.81-3.84) but lower personal engagement (M=3.53). Green brands enjoyed unexpected trust (M=3.86) and premiums paid (M=3.74). Affordability and availability were strongest brakes, with statement "I would buy more if it were more affordable and widely available" highest overall (M=4.04). Conclusion: Consumers show passionate ideological allegiance to eco-fashion but in purchasing decisions prioritize functionality over environmental concerns. The intention-action gap persists not due to awareness gaps but due to structural barriers. Implications: Results show that advocates of sustainable fashion must emphasize practical benefits as well as environmental reasons, while sector players must address cost and access barriers. Policymakers can provide incentives and standardization assistance, and educators must emphasize developing competencies to bridge the intention-action gap for activities like upcycling.